Tingkat Kemandirian Sosial Anak Tk Kelompok B Ditinjau Dari Status Pekerjaan Ibu (Studi Komparatif di TK Se-Kecamatan Manna Kabupaten Bengkulu Selatan) - nadia, elen falen; suryadi, didik; indrawati, indrawati (JURNAL PENA PAUD, 2023)
The purpose of this research was to explain the differences in the degree of social independence of children from working and non-working mothers. The population in this survey is all the children of Group B in Kindergarten in Manna District, South Bengkulu Regency, totaling 189 children. This type of survey is a quantitative survey using the comparative description method. The sample of this research consisted of 57 children who were selected using Purposive random sampling technique. The data collection method for this survey used a questionnaire. Based on the data processing of the calculation results of SPSS version 16, statistical testing of the t test, the results of the T count value of 6.054 and T table of 2.004, with a significance of 0.000. With the test criteria if T count > T table and if the significance value < (0.05), then Ho is rejected and Ha is accepted. So that there is a significant difference between the social independence of group B kindergarten children in working and non-working mothers in Kindergartens throughout Manna District, South Bengkulu Regency.